Temperaturne razmere v mraziščih Komne - Svetlin, Domen (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
The varied surface of mountain landscapes allows for a diverse topoclimate and large gradients of meteorological and climatological elements, including air temperature. The mountain frost hollows show severe temperature conditions with increased amplitudes, especially due to their pronounced minimum values. After 2004, the research of frost hollows in Slovenia received a new impetus, and the previous research, which was mainly focused on vegetation growth conditions, was extended to the field of climatology. Continuous measurements in several frost hollows conducted by researchers from the Slovenian Meteorological Forum resulted in an extensive amount of data and findings on temperature conditions in frost hollows, which we present in more detail in this paper. In addition to the new lowest temperatures measured in Slovenia, it turned out that the annual average temperatures in mountain frost hollows are up to 3 °C lower than in the surrounding area, and the average low temperatures are up to 7 °C. In recent decades, temperatures below -30 °C in Slovenia occurred exclusively in frost hollows, and at altitudes of 1000 and 1500 m this also applies to temperatures below -20 °C. The maximum temperatures in frost hollows are very similar to those outside, they can even be slightly higher.
Keywords: climatogeography; ekstremne temperature; extreme temperatures; gorsko podnebje; Julian Alps; Julijske Alpe; klimatogeografija; Komna; mountain climate; Slovenia; Slovenija; temperature inversion; temperaturni obrat